Selectivity of Ethyl Acetate Fraction of Gynura Procumbens on Colon Cancer and Breast Cancer - Nurulita, Nunuk Aries; Meiyanto, Edy; Sugiyanto, . (Indonesian Research Gateway, 2011)
Gynura procumbens is widely used as traditional remedy in South-East Asia. Gynura procumbens exhibites anti inflammatory, antioxidant, and reduced blood pressure activity. The aim of this study was to determine chromatographic profile of ethyl acetate fraction of Gynura procumbens (FEG) and to investigate its cytotoxic properties and selectivity to colon cancerand breast cancer cancer cells. The chromatographic profile of FEG was determined using HPTLC densitometric and HPLC. MTT (3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was performed to determine the growth inhibitory effect of FEG on the growth of WiDr, MCF-7, and T47D cells. NIH3T3, a normal cells was used to determine the selectivity of FEG, which contained small amount of quercetin as identified from chromatographic profile both HPTLC and HPLC. FEG inhibited cell growth of WiDr, of MCF-7 and of T47D cells in time dependent manner. Quercetin affected cell growth inhibition approximately two fold higher at WiDr and MCF-7, whereas FEG had lower effect on T47D cell. Quercetin did not seem as the main active compound of FEG. At this study, FEG caused less inhibition on the growth of NIH3T3 cells than that of on all cell lines. Selectivity index (SI) of FEG on WiDr, MCF-7 and T47D were 4.97, 2.77 and 7.79 respectively. According to the datas obtained, FEG possesses moderate to high cytotoxicity properties on WiDr, MCF-7 and T47D cells. FEG demonstrates selective effect against cancer cells and reveals prospective properties as cancer chemoprevention agent.Keywords: Gynura procumbens, colon cancer, breast cancer, cytotoxicity, selectivity